IDENTITY OF MAN - Clark, Grahame, 1907-1995. ([S.l.])
1 online resource.
Keywords: First published in 1982 in the Identity of Man Professor Clark considers a problem which has puzzled men from the authors of the books of the Old Testament to Charles Darwin and his successors: how to reconcile the animal appetites of men with their awareness of gods and their intimations of immortality. What is it that differentiates us most decisively from the other Primates? He argues that the distinction is to be found primarily in the fact that, whereas the behaviour of other animals is largely dictated by their genes, we follow (or reject) cultural patterns inherited through belonging to societies shaped by history. Whereas other animals behave in a broadly homogenous way within breeding populations men adhere to the diversity of cultural traditions observed by ethnographers among peoples surviving on their fringes of the modern world and reconstructed by archaeologists from the cultural fossils of antiquity. Grahame Clark has written an original and fascinating study, drawing both on his lifetime's experience of archaeological material and on a wide range of other sources to throw new light on the question of man's identity. This is a must read for archaeologists and anthropologists.